THE SELF-CONCEPT OF GENERATION Z USERS OF THE TIK TOK APPLICATION IN ROKAN HULU REGENCY - Mustaqimmah, Nurul; Sari, Novi Dian (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Self-concept is an individual's view and attitude towards oneself. Self-view is related to physical dimensions, individual characteristics, and self-motivation. The purpose of this study was to determine the self-concept of Generation Z users of the Tik Tok application in Rokan Hulu Regency. This study uses the theory of Looking Glass Self with three indicators as an analytical. This study uses a descriptive qualitative method by interviewing 5 informants, namely Generation Z with an age range of 11 to 23 years. The data collection techniques used in this study were interviews, observation and documentation. The results of this study indicate that the self-concept of Generation Z in Rokan Hulu Regency is a Positive Self-Concept. This study reveals that Generation Z in Rokan Hulu Regency uses the tiktok platform as a tool to gain fame by going viral on social media, becoming an effective promotional media. The perceived self-reflection included the satisfaction of receiving a positive response, receiving praise fairly, accepting criticism and suggestions openly, and wanting to improve themselves with a better collar.